Open Government: The Mandate of Reform That is Still Neglected - Faria Ruhana; Nuphanudin Nuphanudin; Andi Annisa Nurlia Mamonto; Wesley Liano Hutasoit; Fakhry Amin (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Open government, also known as government transparency, is a reform mandate that needs to be handled as soon as possible. The purpose of open government in public policy is to foster transparency, involvement, and accountability. The idea of open government has been the topic of scholarly discussion for only recently, yet it has already gained significant traction. This normative and analytical paradigm can be articulated through conversations centered on the reform of governance. A new normative, strategic, and operative paradigm has emerged from the mandate of reform, which is based on the principles of openness, participation, and collaboration, it is argued in this paper that around the idea of open government and, more precisely, at least in Indonesia, the idea of an open state, a new paradigm has emerged. This paradigm is centered on the idea of open government. This research makes use of a qualitative methodology alongside a method of literature evaluation. This study will inquire into the rebirth of open government as well as the idea of an open state achieved through open government as a mandate for the ongoing fight for reform